A Pragmatic Comparison of Commissive Acts in Grammarly and QuillBot advertisements on YouTube - Vivin Sumanti; Hendi Pratama; Rini Susanti Wulandari (Universitas Islam Negeri Palopo, 2025)
Abstract This study aims to compare the utilization of commissive acts in Grammarly and QuillBot advertisements on YouTube from a pragmatic perspective. In digital advertising, brands often use language to express commitments that influence viewer behavior. However, limited research has focused on how brands strategically use commissive acts to build trust and persuade viewers. This study specifically analyzes how commissive acts like promises, guarantees, and offers are utilized by Grammarly and QuillBot to convey brand commitments and influence viewer perceptions. A qualitative descriptive methods were applied to fourteen video advertisements (seven per brand) published between 2021 and 2025. Each commissive utterance was identified, categorized by type, and analyzed using the illocutionary force indicator device (IFID). The findings revealed 33 guarantees, 24 promises, and 4 offers in the Grammarly advertisements, while QuillBot displayed 14 guarantees, 11 promises, and 26 offers. In addition, ten informants participated in a Likert-scale questionnaire and semi-structured interviews to assess the clarity, persuasiveness, and credibility of commissive messages. The results showed that Grammarly tended to emphasize emotionally driven promises and assurances to build credibility, while QuillBot focused on functional offers related to academic tasks. The informants generally considered Grammarly’s commissive acts clearer and more persuasive, while QuillBot’s were perceived as practical but less emotionally appealing. The study concludes that commissive acts play an important role in digital brand communication and that pragmatic analysis provides valuable insights into how linguistic strategies shape audience responses.